2018
DOI: 10.1007/s00190-018-1134-2
|View full text |Cite
|
Sign up to set email alerts
|

Validating and comparing GNSS antenna calibrations

Abstract: GNSS antennas have no fixed electrical reference point. The variation of the phase centre is modelled and tabulated in antenna calibration tables, which include the offset vector (PCO) and phase centre variation (PCV) for each frequency according to the elevations and azimuths of the incoming signal. Used together, PCV and PCO reduce the phase observations to the antenna reference point. The remaining biases, called the residual offsets, can be revealed by circulating and rotating the antennas on pillars. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The direct comparison of Geo++ and University Bonn IGG products has already been carried out several times by others [ 21 , 41 ], and the authors have shown a very good agreement in L1 patterns and some systematic differences in L2 patterns. This was confirmed in the work of [ 42 ], where the authors also compared these antenna calibrations, but they focused on the estimated position. A two-fold better agreement in the estimated height was derived for the L2 signals rather than the L1 signals.…”
Section: Resultsmentioning
confidence: 55%
“…The direct comparison of Geo++ and University Bonn IGG products has already been carried out several times by others [ 21 , 41 ], and the authors have shown a very good agreement in L1 patterns and some systematic differences in L2 patterns. This was confirmed in the work of [ 42 ], where the authors also compared these antenna calibrations, but they focused on the estimated position. A two-fold better agreement in the estimated height was derived for the L2 signals rather than the L1 signals.…”
Section: Resultsmentioning
confidence: 55%
“…Therefore, we decided to reduce the GNSS data interval from 15 s to 1 s in the 2016 campaign so that the methods to detect and mitigate the multipath error that were being developed at Space Geodesy and Navigation Laboratory of the University College London (SGNL-UCL), which were described in the previous section, could be better implemented and tested. With regard to the GNSS antennas, we always used the same two 3D choke-ring Leica AR25.R4, which were individually calibrated by the University of Bonn by using the anechoic chamber method [52,53]. The two antennas were set up carefully oriented towards the geodetic north which was rigorously realized by benchmarks that are permanently located near every pillar.…”
Section: Description Of the Experimentsmentioning
confidence: 99%
“…The here presented selection of the distribution type and its variability range are solely preliminary steps. At minimum, a GUM analysis of GNSS observations, a much more detailed study of all influencing factors, has to be performed, which is a current project at the Finish Geodetic Institute [12].…”
Section: Approach To Perform a Gum Analysis For Geodetic Observationsmentioning
confidence: 99%
“…The GNSS uncertainty model is just a rough idea, as in general it is difficult to simulate all influence factors with e.g., orbital errors, remaining atmospheric effects, multipath and near field effects. Colleagues from FGI are working on the problem to develop a more realistic GUM model for GNSS, see [12].…”
Section: Input Variables For Gum Analysismentioning
confidence: 99%